Efforts to Improve Students Creative Thinking Abilities in Science Learning: A Review - Mahmudah, Huraiza (AMPLITUDO : Journal of Science and Technology Innovation, 2023)
This research aims to examine efforts that can be made to improve students creative thinking abilities in science learning. The method used is a literature review. The literature review method is used to identify, examine, evaluate, and interpret all available research on the topic area of an interesting phenomenon, with certain relevant research questions. Several learning models that can be used to improve students creative thinking abilities in science learning include project-based learning, problem-based learning¸ talking stick, guided inquiry and pictures and pictures. Searching for articles through literature studies resulted in 25 articles that met the criteria and were relevant for review. The research results show that there are many learning models that can be applied in science learning to improve students creative thinking abilities. Based on the results of literature studies, it shows that the picture and picture learning model is the most effective model for improving students creative thinking abilities, which is characterized by an average achievement of students creative thinking abilities of 93.76. The range for the number of articles with the highest value that often appears is in the 60-80 range.